A rare case of type X dual left anterior descending coronary artery. Issue 5 (November 2019) - Natraj Setty, H.S.; Moorthy, Nagaraja; Venkatappa, Jagadeesh; Ramalingam, Rangarajan; Patil, Shivanand; Raghu, T.R.; Manjunath, C.N.
Abstract: A dual left anterior descending (LAD) coronary artery is a rare, and benign congenital anomaly. In this anomaly, there is the presence of two LADs in the anterior inter ventricular sulcus (AIVS). One of the LADs is a short one that ends high in the AIVS. The other longer one enters the distal AIVS and feeds the apex. To date, 9 types of dual LAD variants, and one novel type X has been reported. Herein, we report a case of type X dual LAD with a literature review. <Learning objective: Dual left anterior descending coronary artery (LAD) is an important coronary anomaly to be aware of by interventional cardiologists to avoid misinterpretation of coronary angiography and surgical complications related to coronary interventions. We report a new variation of type X dual LAD with a literature review.>